Metabolic modifications to Ni excess in L. minor: Role of organic-, amino- and fatty acid profiles. (July 2020) - Sha, Sha; Hu, Dan; Hu, Kaijie; Cheng, Menghua; Zhang, Wei; Xu, Qinsong
Abstract: In this study, the effects of excess nickel (Ni) (100 μM and 200 μM) on growth, antioxidant production, fatty acid, organic and amino acids profiles were examined in Lemna minor L. After 7 days of Ni treatment, chlorosis, growth inhibition and ROS overproduction were observed, accompanied by Ni accumulation. Interestingly, decreased malondialdehyde (MDA) levels were recorded in fronds upon Ni exposure. Fatty acid profiles in Ni-treated L. minor were characterized by increases in saturated- and decreases in unsaturated fatty acids. Ni excess increased the activities of antioxidant enzymes such as superoxide dismutase (SOD), guiacol peroxidase (GPX), and glutathione reductase (GR), and non-enzymatic antioxidants such as glutathione (GSH) and ascorbic acid (AsA); however, deactivation of ascorbate peroxidase (APX) and catalase (CAT) activities were also observed. Disruption of amino acid metabolism in Ni-exposed fronds was evidenced by the accumulation of cysteine, arginine, threonine, valine, isoleucine, leucine, lysine and phenylalanine, as well as reduced levels of tyrosine, alanine, aspartate and proline. Approximately 299%–396%, 139%–254% and 56%–97% concentration increments in citric, malic and oxalic acids, respectively, were concomitantly observed with significant decreases in tartaric, acetic, and fumaric acids in fronds subjected to Ni stress. Taken together, these results indicated that Ni stress induced negative effects on plant physiological, biochemical and morphological processes; however, it is likely that the coordination of metabolites and antioxidants may ameliorate the damaging effects of Ni accumulation. Highlights: Lemna minor can be classified as a poor Ni accumulator under laboratory conditions. Ni excess caused remarkable increase in citric, malic and oxalic acids concentrations. Cys, Thr, Val, Iso, Leu, and Phe account for the Ni accumulation and tolerance. Changes of FA profiles induced by Ni were due to SFA increases and UFA decreases. Antioxidants (AsA and GSH) play a key role in the accumulation of Ni in Lemna minor.